Dynamics of Social Interaction: The Influence of School Environment on Elementary School Student Behavior - Wachid, Abdul; Djubaedi, Dedi; Mulyana, Asep (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: This study investigates the dynamics of social interaction at SDN 2 Danamulya, Plumbon, Cirebon, emphasizing the influence of school conditions on students' social engagement and behavior. Social interaction is essential for character formation and social skill development, with the school environment—encompassing policies, relationships, and facilities—playing a pivotal role. Novelty: This research highlights the specific impact of inclusive policies, teacher-student relationships, and peer interactions in fostering positive social development, providing new insights into how school leadership influences social interactions among students. Methods: Using a case study approach, this research examines how inclusive policies, teacher-student relationships, and peer interactions foster positive social development. Results: The findings, grounded in Social Learning Theory, reveal that students acquire social behaviors through observation, reinforcement, and interaction. School initiatives such as collaborative learning, mentoring programs, and structured reward systems create a supportive environment, with school leadership playing a crucial role in sustaining these interactions. Conclusion: The study underscores the importance of continuously enhancing strategies to promote inclusivity and positive social engagement, though it is limited to the internal school environment and does not account for external social influences.